THE NET PRIMARY PRODUCTION ESTIMATION OF HERBACEOUS PLANTS IN A SIMPLE TERRESTRIAL ECOSYSTEM - Harsoyo Purnomo (Bioma : Jurnal Ilmiah Biologi, 2011)
ABSTRACT The knowledge of net primary production of ?é?áherbaceous plants on certain area is very important?é?á because the net primary production can be used to estimate the envi-ronmental support, estimating the competitiveness of?é?á herbaceous plants (weeds) to-ward the cultivated plants which become problems for farmers. The objective of the study was to investigate: (i). the increase rates of biomass (standing crop) or net primary production per unit area in one month; (ii) estimation of total net primary production of herbaceous plants in research area; ?é?á(iii) the fac-tors that directly affect on continuous gradual change of biomass during research pe-riod; (iv) the community composition of herbaceous plants in research area. The net primary production estimation study was carried out on rubber plantation area Mijen, Semarang. Ten stands were selected subjectively,?é?á and in each stand was placed three permanent plots, each is 40 X 25 cm. From the plot 1 the living and dead plant material should be collected.?é?á From plot 2, all of the living shoot material should be removed but all of the dead plant material left in place. At the end of the production period, the dead shoot material should be collected from plot II and the living shoot material, dead shoot material, and total root material from plot 3. The material should be sorted, and dried at oven at 100o C for 48 hours and weighed. The result of the study shows that there is difference of dry weights (standing crop biomass) on the beginning and the end of research is 9.525 g/plot for living shoot material, and 5.483 g/plot for dead shoot material. Mean of total net production in one month is 25.899 g/plot or 103,596 g-cal/m2. The factors that directly affect on continuous gradual change of biomass during research period is edaphic and climatic factors. The communitycomposition of herbaceous plants in research area was dominated by Brachiaria reptans. The conclusion is that the net primary production in research area was estimated. The continuous gradual change of?é?á biomass during ?é?áresearch period was affected by environmental condition that is edaphic and climatic factors Key words: primary production; herbaceous; biomass; community, ecosystem.